PRESENTATION INFORMATION YOUTH RED CROSS (PMR) PUSPARAJA STATE PUBLIC HIGH SCHOOL 1 THROUGH INTERNET CIPUTAT USING MACROMEDIA FLASHMX - Sandhy Nanda Nugraha; Yuce Yuliani, SKom., MMSI Yuce Yuliani, SKom., MMSI (Jurnal Sistem Informasi, 2006)
Internet as information resources that reach the entire world is information on currentdevelopments. Such information can be presented through the web, and this web canbe more interesting if there is animation or design with a more lively appearance.PMR Pusparaja SMU Negeri 1 Ciputat in providing knowledge about the absurdlyrosy and health to the community and build relationships between fellow members ofthe PMR in SMU Negeri 1 PMR Ciputat and members of other schools, hence madean interesting website with animation and display design more life.